2011
DOI: 10.1017/s0007114510005350
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of electrolyte homeostasis by dietary nitrogen intake in growing goats

Abstract: In goats, the combination of dietary N and Ca reduction caused hypocalcaemia and further changes in Ca homeostasis. The aim of the present study was to characterise the effects of dietary N reduction under normocalcaemia on mineral and bone metabolism in young goats. Young male goats of the Saanen breed were fed a diet reduced in N (8 %) for about 7 weeks (ten animals per group) and were compared with goats fed with an adequate N (14 %) diet. When N intake was reduced in young goats, plasma urea concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 53 publications
3
20
0
Order By: Relevance
“…A detailed description of the study design, feeding system and animals has been described previously (Muscher et al 2011). Briefly, twenty male white Saanen goats, aged about 3 months were randomly divided into two feeding groups consisting of ten animals each.…”
Section: Animals and Feeding Regimesmentioning
confidence: 99%
See 4 more Smart Citations
“…A detailed description of the study design, feeding system and animals has been described previously (Muscher et al 2011). Briefly, twenty male white Saanen goats, aged about 3 months were randomly divided into two feeding groups consisting of ten animals each.…”
Section: Animals and Feeding Regimesmentioning
confidence: 99%
“…Therefore, interplay of aquaporin water channels and urea transporters in the kidney may occur to maintain urea metabolism in times of N scarcity in young goats. about 92 % (Muscher et al 2011). In a former study, it could be shown that an N-reduced diet in young goats led to an upregulation of urea transporter UT-A1 mRNA expression in renal medulla (Starke et al 2012), assuming that this is an important mechanism for saving urea in times of N scarcity.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations